Enoxaparin-Induced DRESS Syndrome - Sophie Ronceray; Monica Dinulescu; François Le Gall; Elisabeth Polard; Alain Dupuy; Henri Adamski (Case Reports in Dermatology, 2012)
Low-molecular-weight heparins are widely used for the prophylaxis and treatment of venous thromboembolism. However, they can induce adverse skin reactions. The most common reactions are delayed-type hypersensitivity reactions at injection sites. Rare systemic reactions have been reported. We report, to our knowledge, the first case of a drug reaction with eosinophilia and systemic symptoms syndrome (DRESS) due to enoxaparin which belongs to the low-molecular-weight heparins class.